The effects of communication apprehension on group performance - L. F. Pitt; D. Nel (South African Journal of Business Management, 1990)
With this study the phenomenon of communication apprehension is considered and the findings of an exploratory study into the effects of communication apprehension on group performance in a computerized marketing decision-making simulation are presented. Despite the many effects of communication apprehension as alluded to in the literature, it is evident from this study that communication apprehension (or absence thereof) among some or all members of a group in participation in a business game has little or no effect on group success.In hierdie studie word die verskynsel van kommunikasievrees oorweeg, en die bevindings van 'n verkennende studie na die gevolge van kommunikasievrees op groepprestasie in 'n gerekenariseerde bemarkings-besluitnemingsimulasie bespreek. Ten spyte van die verskeidenheid gevolge van kommunikasievrees soos in die literatuur bespreek, blyk dit dat kommunikasievrees (of gebrek daaraan) onder al die of sommige van die lede van 'n groep in 'n besigheidspel, geen of 'n klein effek op die prestasie van die groep het.
Keywords: 650